Effect of athletic training on heart rate variability - Cingalek, R.; Bunc, V.; Cingalkova, M. (2001)
Measurement of heart rate (HR) and heart rate variability (HRV) can be used to indicate training effects and has proved to be the best way to notice the beginning state of fatigue and/or overtraining. The purpose of this study was analyze training effects on HR and HRV. The data were collected by Polar Sporttester, type Vantage NV, which enables us to collect the RR intervals. For the evaluation the method of short time data collection was used (256 beats). To indicate the effect of repeated intensive athletic training on HR and HRV we studied 15 young athletes of both sexes (age ranged from 14 to 18 years), members of Czech national triathlon team during two weeks training camp. HR was measure in standard conditions and there was used time and frequency analysis of HRV. Average RR interval, standard deviation of RR interval, RMSSD and pNN50 was calculated (time analysis). Power of VLF, LF and HF, total power and LF/HF ratio is also calculated (frequency analysis). Power Spectral Density was calculated by using autoregressive modeling. Differences between days with hard and easy training were significant for all parameters. In our study a good correlation was found between time and frequency domain variables. According to our data the HRV seems to be suitable for checking and assessment of effect of imposed physical training in non-trained and trained populations and in selected groups of patients.